A Glance at the Construction of Oqsaroy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the Oqsaroy building from the 14th-15th centuries, one of the most unique architectural monuments of Amir Temur and the Timurid era. Renowned for its beauty and grandeur, Oqsaroy stands as a remarkable medieval landmark, comparable to other architectural masterpieces in attracting foreign travelers. The article highlights certain construction details of the complex, relying on historical sources and literature from that period.